Harry Potter et l’expérience d’effroi : L’effet des Détraqueurs - Auriacombe, Éric (Romanica Silesiana)
The series Harry Potter, proposed by Mrs J.K. Rowling, is a good case in order to understand and analyse the emergence of the fear. Harry Potter, traumatized, orphan and mistreated baby is confronted with the dread when he meets “Dementors”. Who are Dementors? How does Harry discover their existence ? Why is Harry more sensitive to the confrontation with the dementor than the other children ? To answer to this question, we shall study the link between the trauma and some kind of depression in early mourning. Those are the “white” depression and the “cryptophorie”. On the other hand, Mrs. Rowling proposed a therapeutic solution to the despair : the production of a “Patronus” and the reference to the paternal function. Key words : Harry Potter, Dementors, fear, depression, early mourning, therapeutic, paternal function